An ancient F-type subdwarf from the halo crossing the Galactic plane - Scholz, R. -D.; Heber, Ulrich; Heuser, Christian; Ziegerer, Eva; Geier, Stephan; Niederhofer, F (Astronomy & Astrophysics, 2015)
Aims. We selected the bluest object, WISE J0725-2351, from Luhman's new high proper motion (HPM) survey based on observations with the Wide-field Infrared Survey Explorer (WISE) for spectroscopic follow-up observations. Our aim was to unravel the nature of this relatively bright (V similar to 12, J similar to 11) HPM star (mu = 267 mas/yr).Methods. We obtained low-and medium-resolution spectra with the European Southern Observatory (ESO) New Technology Telescope (NTT)/EFOSC2 and Very Large Telescope (VLT)/X-Shooter instruments, investigated the radial velocity and performed a quantitative spectral analysis that allowed us to determine physical parameters. The fit of the spectral energy distribution based on the available photometry to low-metallicity model spectra and the similarity of our target to a metal-poor benchmark star (HD 84937) allowed us to estimate the distance and space velocity.Results. As in the case of HD 84937, we classified WISE J0725-2351 as sdF5: or a metal-poor turnoff star with [Fe/H] = -2.0 +/- 0.2, T-eff = 6250 +/- 100 K, log g = 4.0 +/- 0.2, and a possible age of about 12 Gyr. At an estimated distance of more than 400 pc, its proper motion translates to a tangential velocity of more than 500 km s(-1). Together with its constant (on timescales of hours, days, and months) and large radial velocity (about +240 km s(-1)), the resulting Galactic restframe velocity is about 460 km s(-1), implying a bound retrograde orbit for this extreme halo object that currently crosses the Galactic plane at high speed.
Keywords: proper motions; stars: distances; stars: kinematics and dynamics; stars: Population II; subdwarfs; white dwarfs

Binaries discovered by the MUCHFUSS project: SDSS J162256.66 + 473051.1: An eclipsing subdwarf B binary with a brown dwarf companion - Schaffenroth, Veronika; Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Ziegerer, Eva; Heuser, Christian; Classen, Lew; Cordes, O. (Astronomy & Astrophysics, 2014)
Hot subdwarf B stars (sdBs) are core helium-burning stars located on the extreme horizontal branch. About half of the known sdB stars are found in close binaries. Their short orbital periods of 1.2 h to a few days suggest that they are post common-envelope systems. Eclipsing hot subdwarf binaries are rare but are important in determining the fundamental stellar parameters. Low-mass companions are identified by the reflection effect. In most cases, the companion is a main sequence star near the stellar mass limit. Here, we report the discovery of an eclipsing hot subdwarf binary SDSS J162256.66+473051.1 (J1622) with very short orbital period (0.0697 d), which has been found in the course of the MUCHFUSS project. The lightcurve shows grazing eclipses and a prominent reflection effect. An analysis of the light-and radial velocity (RV) curves indicated a mass ratio of q = 0.1325, an RV semi-amplitude K = 47.2 km s -1, and an inclination of i = 72.33°. We show that a companion mass of 0.064 MŠ(tm), which is well below the hydrogen-burning limit, is the most plausible solution, which implies a mass close to the canonical mass (0.47 MŠ(tm)) of the sdB star. Therefore, the companion is a brown dwarf, which has not only survived the engulfment by the red-giant envelope but also triggered its ejection and enabled the sdB star to form. The rotation of J1622 is expected to be tidally locked to the orbit. However, J1622 rotates too slowly (vrot = 74.5 ± 7 kmâ‰ s-1) to be synchronized, challenging tidal interaction models. © 2014 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: eclipsing; Binaries: spectroscopic; Brown dwarfs; Stars: fundamental parameters; Subdwarfs

Hot subdwarf binaries from the MUCHFUSS project Analysis of 12 new systems and a study of the short-period binary population - Kupfer, Thomas; Geier, S.; Heber, Ulrich; Ostensen, R. H.; Barlow, B. N.; Maxted, P. F. L.; Heuser, Christian; Schaffenroth, Veronika; Gaensicke, B. T. (Astronomy & Astrophysics, 2015)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions like massive white dwarfs (M > 1.0 M-circle dot), neutron stars, or stellar-mass black holes. The existence of such systems is predicted by binary evolution theory, and recent discoveries indicate that they exist in our Galaxy. We present orbital and atmospheric parameters and put constraints on the nature of the companions of 12 close hot subdwarf B star (sdB) binaries found in the course of the MUCHFUSS project. The systems show periods between 0.14 and 7.4 days. In nine cases the nature of the companions cannot be constrained unambiguously whereas three systems most likely have white dwarf companions. We find that the companion to SDSS J083006.17+475150.3 is likely to be a rare example of a low-mass helium-core white dwarf. SDSS J095101.28+034757.0 shows an excess in the infrared that probably originates from a third companion in a wide orbit, which makes this system the second candidate hierarchical triple system containing an sdB star. SDSS J113241.58-063652.8 is the first helium deficient sdO star with a confirmed close companion. This study brings to 142 the number of sdB binaries with orbital periods of less than 30 days and with measured mass functions. We present an analysis of the minimum companion mass distribution and show that it is bimodal. One peak around 0.1 M-circle dot corresponds to the low-mass main sequence (dM) and substellar companions. The other peak around 0.4 M-circle dot corresponds to the white dwarf companions. The derived masses for the white dwarf companions are significantly lower than the average mass for single carbon-oxygen white dwarfs. In a T-eff - log g diagram of sdB+dM companions, we find signs that the sdB components are more massive than the rest of the sample. The full sample was compared to the known population of extremely low-mass white dwarf binaries as well as short-period white dwarfs with main sequence companions. Both samples show a significantly different companion mass distribution indicating either different selection effects or different evolutionary paths. We identified 16 systems where the dM companion will fill its Roche Lobe within a Hubble time and will evolve into a cataclysmic variable; two of them will have a brown dwarf as donor star. Twelve systems with confirmed white dwarf companions will merge within a Hubble time, two of them having a mass ratio to evolve into a stable AMCVn-type binary and another two which are potential supernova Ia progenitor systems. The remaining eight systems will most likely merge and form RCrB stars or massive C/O white dwarfs depending on the structure of the white dwarf companion.
Keywords: subdwarfs; binaries: close

Sub-stellar companions of intermediate-mass stars with CoRoT: CoRoT-34b, CoRoT-35b, and CoRoT-36b - Sebastian, Daniel; Guenther, E. W.; Deleuil, M.; Dorsch, Matti; Heber, Ulrich; Heuser, Christian; Gandolfi, D.; Grziwa, S.; Deeg, H. J.; Alonso, R.; Bouchy, F.; Csizmadia, Sz; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
Theories of planet formation give contradicting results of how frequent close-in giant planets of intermediate mass stars (IMSs; 1.3 <= M-* <= 3.2 M-circle dot) are. Some theories predict a high rate of IMSs with close-in gas giants, while others predict a very low rate. Thus, determining the frequency of close-in giant planets of IMSs is an important test for theories of planet formation. We use the CoRoT survey to determine the absolute frequency of IMSs that harbour at least one close-in giant planet and compare it to that of solar-like stars. The CoRoT transit survey is ideal for this purpose, because of its completeness for gas-giant planets with orbital periods of less than 10 d and its large sample of main-sequence IMSs. We present a high precision radial velocity follow-up programme and conclude on 17 promising transit candidates of IMSs, observed with CoRoT. We report the detection of CoRoT-34b, a brown dwarf close to the hydrogen burning limit, orbiting a 1.1 Gyr A-type main-sequence star. We also confirm two inflated giant planets, CoRoT-35b, part of a possible planetary system around a metal-poor star, and CoRoT-36b on a misaligned orbit. We find that 0.12 +/- 0.10 per cent of IMSs between 1.3 <= M-* <= 1.6 M-circle dot observed by CoRoT do harbour at least one close-in giant planet. This is significantly lower than the frequency (0.70 +/- 0.16 per cent) for solar-mass stars, as well as the frequency of IMSs harbouring long-period planets (similar to 8 per cent).
CRIS-Team WoS Importer:2022-09-09

The catalogue of radial velocity variable hot subluminous stars from the MUCHFUSS project - Geier, S.; Kupfer, Thomas; Heber, Ulrich; Schaffenroth, Veronika; Barlow, B. N.; Ostensen, R. H.; O'Toole, S. J.; Ziegerer, Eva; Heuser, Christian; Maxted, P. F. L.; Gaensicke, B. T.; Marsh, T. R.; et al. (Astronomy & Astrophysics, 2015)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims to find sdBs with compact companions such as massive white dwarfs, neutron stars, or black holes. Here we provide classifications, atmospheric parameters, and a complete radial velocity (RV) catalogue containing 1914 single measurements for a sample of 177 hot subluminous stars discovered based on SDSS DR7; 110 stars show significant RV variability, while 67 qualify as candidates. We constrain the fraction of close massive compact companions of hydrogen-rich hot subdwarfs in our sample to be smaller than ∼1.3%, which is already close to the theoretical predictions. However, the sample might still contain such binaries with longer periods exceeding ∼8 d. We detect a mismatch between the ΔRVmax-distribution of the sdB and the more evolved sdOB and sdO stars, which challenges our understanding of their evolutionary connection. Furthermore, irregular RV variations of unknown origin with amplitudes of up to ∼180 km s-1 on timescales of years, days, and even hours have been detected in some He-sdO stars. They might be connected to irregular photometric variations in some cases.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: atmospheres; Stars: horizontal-branch; Subdwarfs

The catalogue of radial velocity variable hot subluminous stars from the MUCHFUSS project (vol 577, pg A26, 2015) - Geier, S.; Kupfer, T.; Heber, Ulrich; Schaffenroth, Veronika; Barlow, B. N.; Ostensen, R. H.; O'Toole, S. J.; Ziegerer, Eva; Heuser, Christian; Maxted, P. F. L.; Gansicke, B. T.; Marsh, T. R.; et al. (Astronomy & Astrophysics, 2017)
Keywords: binaries: spectroscopic; subdwarfs; stars: horizontal branch; stars: atmospheres; errata; addenda

The subdwarf B star SB 290-A fast rotator on the extreme horizontal branch - Geier, Stephan; Heber, Ulrich; Heuser, Christian; Classen, Lew; O'Toole, S. J.; Edelmann, Heinz (Astronomy & Astrophysics, 2013)
Hot subdwarf B stars (sdBs) are evolved core helium-burning stars with very thin hydrogen envelopes. To form an sdB, the progenitor has to lose almost all of its hydrogen envelope right at the tip of the red giant branch. In close binary systems, mass transfer to the companion provides the extraordinary mass loss required for their formation. However, apparently single sdBs exist as well, and their formation has been unclear for decades. The merger of helium white dwarfs leading to an ignition of core helium-burning or the merger of a helium core and a low-mass star during the common envelope phase have been proposed. Here we report the discovery of SB 290 as the first apparently single, fast-rotating sdB star located on the extreme horizontal branch, indicating that those stars may form from mergers. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Stars: rotation; Subdwarfs